The Digital Evolution: Exploring the Impact of Digital Transformation on Employee Job Satisfaction through Bibliometric Analysis - Loso Judijanto; Fachrizal Anwar; Erwin Setiawan; Unika Oktaviani Damau; Moh Gifari Sono (West Science Business and Management, 2024)
This study employs a bibliometric analysis to investigate the relationship between digital evolution and employee job satisfaction. As digital technologies like artificial intelligence, big data, and the Internet of Things become increasingly prevalent in the workplace, their impact on job satisfaction is both significant and multifaceted. The analysis identified central themes such as technological empowerment, organizational support, and the necessity of adaptive leadership. It revealed that while digital tools enhance job satisfaction by providing greater autonomy and flexibility, they also introduce challenges such as job insecurity and potential overload without proper management. Organizational support in the form of training and effective leadership was found to be critical in facilitating a positive transition into digitalized work environments. This study not only highlights the complex dynamics of digital transformation in the workplace but also suggests that the careful management of digital tools and strategies can enhance job satisfaction. Future research directions include longitudinal studies on the long-term effects of digital technologies across different industries and cultural contexts.